Abundant cytomegalovirus (CMV) reactive clonotypes in the CD8+ T cell receptor alpha repertoire following allogeneic transplantation. (8th March 2016) - Link, C S; Eugster, A; Heidenreich, F; Rücker-Braun, E; Schmiedgen, M; Oelschlägel, U; Kühn, D; Dietz, S; Fuchs, Y; Dahl, A; Domingues, A M J; Klesse, C; et al.
Summary: Allogeneic stem cell transplantation is potentially curative, but associated with post-transplantation complications, including cytomegalovirus (CMV) infections. An effective immune response requires T cells recognizing CMV epitopes via their T cell receptors (TCRs). Little is known about the TCR repertoire, in particular the TCR-α repertoire and its clinical relevance in patients following stem cell transplantation. Using next-generation sequencing we examined the TCR-α repertoire of CD8 + T cells and CMV-specific CD8 + T cells in four patients. Additionally, we performed single-cell TCR-αβ sequencing of CMV-specific CD8 + T cells. The TCR-α composition of human leucocyte antigen (HLA)-A*0201 CMVpp65– and CMVIE -specific T cells was oligoclonal and defined by few dominant clonotypes. Frequencies of single clonotypes reached up to 11% of all CD8 + T cells and half of the total CD8 + T cell repertoire was dominated by few CMV-reactive clonotypes. Some TCR-α clonotypes were shared between patients. Gene expression of the circulating CMV-specific CD8 + T cells was consistent with chronically activated effector memory T cells. The CD8 + T cell response to CMV reactivation resulted in an expansion of a few TCR-α clonotypes to dominate the CD8 + repertoires. These results warrant further larger studies to define the ability of oligoclonally expanded T cell clones to achieve an effective anti-viral T cell response in this setting.